2014
DOI: 10.1371/journal.pone.0107500
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Boreal Rivers in Providing Iron to Marine Waters

Abstract: This study reports increasing iron concentrations in rivers draining into the Baltic Sea. Given the decisive role of iron to the structure and biogeochemical function of aquatic ecosystems, this trend is likely one with far reaching consequences to the receiving system. What those consequences may be depends on the fate of the iron in estuarine mixing. We here assess the stability of riverine iron by mixing water from seven boreal rivers with artificial sea salts. The results show a gradual loss of iron from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 77 publications
10
66
0
Order By: Relevance
“…The concentration of TDFe in current study is comparable with that in the boreal blackwater rivers which are commonly characterized by a high TDFe content (Regina et al, 2010;Kritzberg et al, 2014). This may be attributed to the geological conditions of the Songhua River Basin surrounded by orogenic zones which are filled with iron-rich terrigenous sedimentary, volcanogenic, and intrusive rocks.…”
Section: Concentration and Output Of Tdfesupporting
confidence: 81%
“…The concentration of TDFe in current study is comparable with that in the boreal blackwater rivers which are commonly characterized by a high TDFe content (Regina et al, 2010;Kritzberg et al, 2014). This may be attributed to the geological conditions of the Songhua River Basin surrounded by orogenic zones which are filled with iron-rich terrigenous sedimentary, volcanogenic, and intrusive rocks.…”
Section: Concentration and Output Of Tdfesupporting
confidence: 81%
“…Recent experiments also have shown a change in dissolved organic matter (DOM) quality in river water treated with saline solutions. Kritzberg et al (2014) found that high salinity caused a decrease in humic acids and aromatic DOM (as indicated by E4/E6 and SUVA 254 , respectively), and riverine average molecular weight has been observed to decrease even at low salinities (1-6; Asmala et al 2014b). Similarly in freshwaters it is the hydrophobic component of humic and fulvic acids that is the most reactive (Sharp et al 2006), and in coloured waters this fraction constitutes 60-80 % of the total DOC (Malcolm 1985), indicating significant potential for flocculation when DOC-rich waters enter estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…Also land use changes such as ditching and forest clearance have influenced the inputs of particulate material to the coastal zone (Yu et al, 2015). Moreover, the transport of riverine Fe and DOM into the Baltic has increased in recent decades as a consequence of brownification (Kritzberg et al, 2014), related primarily to the recovery of boreal freshwater systems from industrial acidification in the mid-20 th century (Monteith et al, 2007). These changes may be expected to influence both the sediment composition and diagenetic processes in the sediments at our study sites through time.…”
Section: Temporal Stability Of Flocculation Impacts On Sedimentationmentioning
confidence: 99%
“…This component may be more substantial than previously thought and hence play a role in providing Fe as a micronutrient to the oceans (Kritzberg et al, 2014;Krachler et al, 2016). However, the majority of dissolved Fe in river water is associated with higher-molecular weight DOM, hence most riverine dissolved Fe is retained by flocculation in estuaries (Raiswell, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation